Determination of activity concentration of Radon-222 by using its daughter progeny Pb-214 and bi-214 in water by using Gamma spectrometry / Elly Munirah Marzuki - Marzuki, Elly Munirah (Faculty of Applied Sciences, 2009)
In this thesis, low background gamma ray spectrometer has been applied to determine the activity concentration of radon-222 in water collected from ex-mining’s lake at Universiti Teknologi MARA Training Centre, Kampung Gajah, Perak. This is simple method, where we just only measure the sample waters with a germanium (Ge) detector using the gamma rays spectrometer from the radon-222 daughter nuclides Pb-214 and Bi-214. Sample water collected are directly pour into Marinelli beaker and sealed and stored for 3 weeks to allow radon-222 and daughter nuclides were in radioactive equilibrium before counting. The radon activity concentration is determined by taking the average weighed of the concentrations derived from γ-ray lines associated with Pb-214 and Bi-214 decay. We cannot direct counting radon-222 by using gamma spectrometry because it’s not emitted gamma radiation, but it’s is alpha emitted radionuclides. In this study, the activity concentration of radon-222 is higher at location 11 either for unfiltered and filtered water samples, which is 4429 Bq/L for unfiltered and 10015 Bq/L for filtered water samples. While, the lowest activity concentration of radon-222 for unfiltered and filtered water samples was investigated at location 1 and location 2 with the values 1328 Bq/L and 3308 Bq/L respectively. The activity concentration of radon-22 in this study area is higher and need more attention from related authorities because it can give higher percentage of risk of radiation at that area.